Empowering the Banjar Indra Giri Community Through the Use of Used Bottles as a Medium for Creative Economy Education in Sangiang Hamlet - I Made Widiarsana Putra; I Nyoman Wijaya; I Putu Gede Asnawa Dikta; I Komang Widya Purnama Yasa (Faculty of Engineering UNHAS, 2025)
The problem of waste, especially plastic, has become an urgent environmental issue due to its difficulty in decomposing and its negative impact on the ecosystem. The activity “Empowering the Banjar Indra Giri Community through the Use of Used Bottles as a Medium for Creative Economic Education in Sangiang Hamlet” was carried out to provide a solution to this problem while also improving the community's financial literacy. The main objectives of this activity were to foster awareness and skills in managing plastic waste into products of economic value and to instill the habit of saving from an early age through a creative approach. The methods used included participatory observation, direct demonstrations, and evaluation with pre-test and post-test instruments to measure changes in participants' knowledge, attitudes, and skills. The quantitative results show a significant increase in all aspects assessed. The average pre-test score of 59 indicates a relatively low level of initial understanding, while the average post-test score increased to 91, indicating an increase of 54%. In detail, the aspect of understanding the importance of saving increased from 56 to 88, knowledge of plastic waste management from 60 to 90, creativity in making recycled products from 58 to 92, and environmental awareness from 62 to 94. These results show that the training program not only improved participants' cognitive abilities, but also encouraged positive behavioral changes in environmental management and financial habits. Qualitatively, the activity of making piggy banks from used bottles became a fun and meaningful educational tool for children. They learned to save money, hone their creativity, and understand the economic and ecological value of recycling. This program has succeeded in fostering a younger generation that is more independent, thrifty, and environmentally conscious. Thus, this empowerment activity has proven to be an effective model for creative economy-based community development that integrates environmental education and financial literacy to support sustainable development.